YIELD TO MATURITY BOND: INTEREST RATE, INFLATION AND BOND RATING – EMPIRICAL RESEARCH ON BANKING SECTOR - Listiya Ike Purnomo; Mila Wijaya; Elfan Pratama (JRAK, 2022)
This research aims at determining the impact of interest rates, inflation and bond rating on bond yields to maturity. This type of exploration using quantitative exploration with an associative approach. purposive sampling was used for the selection of research samples. The population of this research is banking companies listed on the Indonesia Stock Exchange in 2016-2020. This disquisition used panel data regression analysis system. From the model test, a random effect model was attained as a model estimator. The result of this research is that interest rates, inflation, and bond rating together affect bond yields to maturity. Interest rate and inflation variables did not affect a bond's yield to maturity. The bond standing variable harms the bond's yield to maturity.